Streptococcus MutansInfections in Infants and Related Maternal and Child Factors - Blerta Latifi-Xhemajli; Aida Rexhepi; Jacques Veronneau; Teuta Kutllovci; Dafina Ahmeti; Shqiprim Bajrami (University of Zagreb. School of Dental Medicine, 2021)
Objective: The aim of the study was to investigate the maternal-child S. mutans infection, mutual interaction and potential risk factors altering this interaction. Material and methods: A total of 160 mothers who were paired with their children were recruited. Saliva from mothers and children was collected and S. mutans categorized levels were analyzed. A questionnaire was used to collect maternal and child conventional caries risk factors. A proportional odds regression model was used to investigate whether the level of infection of mothers would similarly affect the level of infection of their children, thus adjusting for other risk factors. Results: The average age of mothers was 28.1 years and children had a median age of 5.1 months. Paired mother-child S. mutans crossclassification into non-infected and infected subjects showed no agreement in mutual contamination. Maternal in-fection of the child was highest when the mother was infected with 10 >3 S. mutans/ml of saliva. The results obtained by the regression model showed that none of the potential risk factors influenced the level of infection in the child. Conclusion: Mothers with a high S. mutans level increase the risk of S. mutans acquisition for her five- month- old child but no evidence was found that other maternal/ child factors may influence this.